Construction costs and energy consumptions resulting from energy retrofitting in a residential building in Madrid (Spain) - García Navarro, Justo; González Díaz, María Jesús; Valdivieso Rodríguez, Marta (Revista de la Construcción. Journal of Construction, 2013)
This theoretical study analyses the relation between the needed measures for the energy retrofitting of a residential building constructed in Madrid, their cost and the improvement of the energy rating of the dwellings. The aim of this work is to develop proposals and solutions for building’s energy retrofitting that help developers and designers in the decision-making process. In this case study 2 passive systems (acting on the envelope), 13 active systems (regarding energy systems), and the needed combinations between all of them, have been taken into account. Consequently, 26 hypothesis of energy retrofitting, with their respective energy rates, have been analyzed. All of them have been assessed not only from a cost-benefit approach, but also considering consumes and CO2 emissions. This study will allow finding the most suitable cost-effective solutions in each case. Energy retrofitting means an increase in property value but it can’t be only considered in economic terms. It is necessary to take into account other unquantifiable aspects as increased comfort, improved sound insulation, livability, health, or the elimination of energy poverty situations.